Beyond competence: an essay on a process approach to organising and enacting vocational education. (1st September 2016) - Billett, Stephen
Abstract: The competency-based approach to vocational education is premised on narrow and dated conceptions of human functioning, performance and development. Its adoption is more driven by administrative concerns about measurable outcomes than educational processes and outcomes. Informed by educational science and earlier debates, this article discusses the goals for and approaches to realising the outcomes that governments and supra-governmental agencies want. It emphasises the centrality of (1) experiences promoting students' learning, (2) understanding the goals to be achieved by vocational education, and (3) aligning these with educational processes. Common to individuals, their communities, workplaces, professional associations and government needs are the development of applicable and adaptable occupational capacities. Yet these cannot be secured or assessed through competency-based education. The capacities required for current and emerging occupational practice necessitate a focus upon processes, not measurable outcomes. Hence, there is need to focus on learners' personal practices and educational processes.